Immunohistochemical study on the neuroendocrine system of the digestive tract of turbot, Scophthalmus maximus (L.), infected by Enteromyxum scophthalmi (Myxozoa) - R. Bermudez; F. Vigliano; M. I. Quiroga; J. M. Nieto; G. Bosi; C. Domeneghini (Fish & Shellfish Immunology, 2007)
In recent years a new parasite, causing severe losses, has been detected in farmed turbot, Scophthalmus maximus (L.), in Northwestern Spain. Dead fish showed emaciation and cachexia caused by severe necrotizing enteritis, which affected all areas of the digestive tract. The parasite was classified as a myxosporean and named Enteromyxum scophthalmi. This study was designed to assess the response of the turbot neuroendocrine system against E. scophthalmi infection. Immunohistochemical tests were applied to sections of the gastrointestinal tract of uninfected and E. scophthalmi-infected turbot, and the presence of cholecystokinin (CCK-8), serotonin (5-HT), substance P (SP), calcitonin gene-related peptide (CGRP) and vasoactive intestinal peptide (VIP) were documented. A higher abundance of both endocrine epithelial cells (ECs) and nerve cell bodies and fibres for CCK-8, 5-HT and SP were recorded in the gastrointestinal tract of infected turbot, whereas VIP-like substance decreased. The results indicate that E. scophthalmi infection in turbot induced changes in the neuroendocrine system, which may cause alterations in gut motility, electrolyte and fluid secretion, and vascular and immune functions.